ONE-STOP SERVICE AT MUNICIPAL LEVEL: A BUSINESS REFORM IN INDONESIA - Yuli Tirtariandi El Anshori; Enceng Enceng; Ridho Harta (http://jurnal.untirta.ac.id/index.php/JIPAGS, 2017)
Abstract In 2013, Indonesia was ranked 128 of 189 countries in ease of doing business aspect. Many improvements should be undertaken such as doing innovation through One-Stop Service (OSS) in the field of licensing. This article analyzes the implementation of OSS in Indonesia, particularly in Bangka Regency and South Tangerang City. The research method is a qualitative approach. Data are collected by interviews, observations, and related documents. The study shows that OSS can improve public service in Indonesia as the services become more effective and efficient. However, there are some problems in implementing OSS such as the rule of law, human resources, and infrastructures. OSS makes the business reform runs well and increasing the investment growth. Keywords : innovation, public service, business